Exposure to Violence and Carotid Artery Intima‐Media Thickness in Mexican Women - Mario H. Flores‐Torres; Rebekka Lynch; Ruy Lopez‐Ridaura; Elsa Yunes; Adriana Monge; Eduardo Ortiz‐Panozo; Carlos Cantu‐Brito; Arna Hauksdóttir; Unnur Valdimarsdóttir; Martín Lajous (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundViolence against women has become a global public health threat. Data on the potential impact of exposure to violence on cardiovascular disease are scarce. Methods and ResultsWe evaluated the association between exposure to violence and subclinical cardiovascular disease in 634 disease‐free women from the Mexican Teachers' Cohort who responded to violence‐related items from the Life Stressor Checklist and underwent measures of carotid artery intima‐media thickness in 2012 and 2013. We defined exposure to violence as having ever been exposed to physical and/or sexual violence. Intima‐media thickness was log‐transformed, and subclinical carotid atherosclerosis was defined as intima‐media thickness ≥0.8 mm or plaque. We used multivariable linear and logistic regression models adjusted for several potential confounders. Mean age was 48.9±4.3 years. Close to 40% of women reported past exposure to violence. The lifetime prevalence of sexual violence was 7.1%, and prevalence of physical violence was 23.5% (7.7% reported both sexual and physical violence). Relative to women with no history of violence, exposure to violence was associated with higher intima‐media thickness (adjusted mean percentage difference=2.4%; 95% confidence interval 0.5, 4.3) and subclinical atherosclerosis (adjusted odds ratio=1.60; 95% confidence interval 1.10, 2.32). The association was stronger for exposure to physical violence, especially by mugging or physical assault by a stranger (adjusted mean % difference=4.6%; 95% confidence interval 1.8, 7.5, and odds ratio of subclinical carotid atherosclerosis=2.06; 95% confidence interval 1.22, 3.49). ConclusionsExposure to violence, and in particular assault by a stranger, was strongly associated with subclinical cardiovascular disease in Mexican middle‐aged women.